2021
DOI: 10.3390/ijms22105257
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Nonspecific Alkaline Phosphatase in Central Nervous System Health and Disease: A Focus on Brain Microvascular Endothelial Cells

Abstract: Tissue-nonspecific alkaline phosphatase (TNAP) is an ectoenzyme bound to the plasma membranes of numerous cells via a glycosylphosphatidylinositol (GPI) moiety. TNAP’s function is well-recognized from earlier studies establishing its important role in bone mineralization. TNAP is also highly expressed in cerebral microvessels; however, its function in brain cerebral microvessels is poorly understood. In recent years, few studies have begun to delineate a role for TNAP in brain microvascular endothelial cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…As the isozyme name “tissue-nonspecific” implies, TNALP is expressed ubiquitously and modified by post-translational glycosylation processes, to become isoforms that provide significant proteomic diversity and specificity relating to various tissues and cells. The highest levels of human TNALP isoforms are expressed in bone, liver, and kidney tissues [ 1 ]; with neutrophil granulocytes [ 5 ], brain [ 6 ], and vascular cells [ 7 ] as secondary sources of TNALP activity.…”
Section: Biology and Structure Of Alp Isozymes And Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the isozyme name “tissue-nonspecific” implies, TNALP is expressed ubiquitously and modified by post-translational glycosylation processes, to become isoforms that provide significant proteomic diversity and specificity relating to various tissues and cells. The highest levels of human TNALP isoforms are expressed in bone, liver, and kidney tissues [ 1 ]; with neutrophil granulocytes [ 5 ], brain [ 6 ], and vascular cells [ 7 ] as secondary sources of TNALP activity.…”
Section: Biology and Structure Of Alp Isozymes And Isoformsmentioning
confidence: 99%
“…The underlying mechanisms may include a disturbance of vitamin B6 metabolism, since pyridoxal 5′-phosphate, the active form of vitamin B6, is an endogenous substrate for ALP and important for neuronal function in the brain [ 64 ]. In addition, ALP is also involved in cerebral neurotransmission [ 65 ] and contributes to the integrity of the blood–brain barrier [ 6 , 66 ]. While there may be a physiologic role for increased ALP in acute inflammatory states, e.g., sepsis, where increased ALP is associated with improved short-term outcome [ 67 , 68 ], elevated ALP in chronic disease is invariably associated with negative outcomes.…”
Section: The Role Of Alp/balp In Inflammation Metabolic Syndrome and ...mentioning
confidence: 99%
“…Apart from the different clinical characteristics from our included population, some previous basic investigations showed that low ALP levels could increase the amount of inhibitory pyrophosphate resulting in abnormal metabolism of pyridoxine-5 '-phosphate (the main form of vitamin B6) and hypomineralization of the skeleton. The loss of mineralization could cause a variety of symptoms including softening of bone, bowing and spontaneous breakage of bones, rickets and tooth defects [ 23 , 24 ]. However, whether the reduced ALP level could be associated with poor 3-month prognosis in AIS patient with preserved renal function needs to be further explored and verified by subsequent relevant basic experiments.…”
Section: Discussionmentioning
confidence: 99%
“…11 The TNAP protein is commonly found in bones, intestines, livers and brains. 23 As well as playing a role in inflammatory processes, ALP causes cerebral stroke, which is also an inflammatory injury to brain cells. 24 ALP deactivates ATP production, which is a dangerous signal for injury of cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 TNAP is found in brain tissues and the nervous system. 12 In the brain, TNAP is responsible for the development of various tissues, such as the myelin sheath. Under the influence of TNAP, different neurotransmitters are synthesized and regulated.…”
Section: Introductionmentioning
confidence: 99%